Are sexual media exposure, parental restrictions on media use and co‐viewing TV and DVDs with parents and friends associated with teenagers' early sexual behaviour?. Issue 6 (3rd October 2013) - Parkes, Alison; Wight, Daniel; Hunt, Kate; Henderson, Marion; Sargent, James
Abstract: Sexual content in teenagers' media diets is known to predict early sexual behaviour. Research on sexual content has not allowed for the social context of media use, which may affect selection and processing of content. This study investigated whether sexual media content and/or contextual factors (co‐viewing, parental media restrictions) were associated with early sexual behaviour using 2251 14–15 year‐olds from Scotland, UK. A third ( n = 733) reported sexual intercourse. In multivariable analysis the likelihood of intercourse was lower with parental restriction of sexual media and same‐sex peer co‐viewing; but higher with mixed‐sex peer co‐viewing. Parental co‐viewing, other parental restrictions on media and sexual film content exposure were not associated with intercourse. Findings suggest the context of media use may influence early sexual behaviour. Specific parental restrictions on sexual media may offer more protection against early sex than other restrictions or parental co‐viewing. Further research is required to establish causal mechanisms.